The Influence of (5′R)- and (5′S)-5′,8-Cyclo-2′-Deoxyadenosine on UDG and hAPE1 Activity. Tandem Lesions are the Base Excision Repair System’s Nightmare - Karwowski, Bolesław T. (Cells, 2019)
DNA lesions are formed continuously in each living cell as a result of environmental factors, ionisation radiation, metabolic processes, etc. Most lesions are removed from the genome by the base excision repair system (BER). The activation of the BER protein cascade starts with DNA damage recognition by glycosylases. Uracil-DNA glycosylase (UDG) is one of the most evolutionary preserved glycosylases which remove the frequently occurring 2′-deoxyuridine from single (ss) and double-stranded (ds) oligonucleotides. Conversely, the unique tandem lesions (5′R)- and (5′S)-5′,8-cyclo-2′-deoxyadenosine (cdA) are not suitable substrates for BER machinery and are released from the genome by the nucleotide excision repair (NER) system. However, the cyclopurines appearing in a clustered DNA damage structure can influence the BER process of other lesions like dU. In this article, UDG inhibition by 5′S- and 5′R-cdA is shown and discussed in an experimental and theoretical manner. This phenomenon was observed when a tandem lesion appears in single or double-stranded oligonucleotides next to dU, on its 3′-end side. The cdA shift to the 5′-end side of dU in ss-DNA stops this effect in both cdA diastereomers. Surprisingly, in the case of ds-DNA, 5′S-cdA completely blocks uracil excision by UDG. Conversely, 5′R-cdA allows glycosylase for uracil removal, but the subsequently formed apurinic/apyrimidinic (AP) site is not suitable for human AP-site endonuclease 1 (hAPE1) activity. In conclusion, the appearance of the discussed tandem lesion in the structure of single or double-stranded DNA can stop the entire base repair process at its beginning, which due to UDG and hAPE1 inhibition can lead to mutagenesis. On the other hand, the presented results can cast some light on the UDG or hAPE1 inhibitors being used as a potential treatment.